Social support patterns of collegiate athletes before and after injury - Yang, J.; Peek-Asa, C.; Lowe, J. B.; Heiden, E.; Foster, D.T. (Journal of Athletic Training, 2010)
Context: Social support has been identified as an important factor in facilitating recovery from injury. However, no previous authors have prospectively assessed the change in social support patterns before and after injury.